Perspektif Kualitatif Terhadap Efektivitas Strategi Pemasaran dalam Menarik Konsumen di Era Digital pada UMKM Cemilis Jember - Qotrunnada Nur Jihan Adila; Ahmad Sauqi; Hamzah Fansuri Jusuf (GLOBAL SCIENTS PUBLISHER, 2026)
SMEs face challenges in designing effective marketing strategies in the digital era due to limited resources and the absence of structured evaluation. This study aims to identify the marketing strategies applied by Cemilis Jember, an SME, in attracting consumers, evaluate their impact on sales growth, and examine efforts to build and maintain consumer loyalty. This study employs a descriptive qualitative approach with a phenomenological strategy, involving four main informants and one supporting informant from the consumer side, selected through purposive sampling. Data were collected through in-depth interviews, observation, and documentation, then analyzed using NVivo 12 Pro. Findings show that consistently uploading video content on TikTok is the most effective strategy in attracting consumers and significantly increases sales, while consumer loyalty is maintained through responsive service on social media and active communication via WhatsApp. This study concludes that local SMEs can implement structured, impactful digital marketing strategies without a large budget.